Scientific Review of The Sumatran Striped Rabbit (Nesolagus netscheri) Based on Student Knowledge and Awareness - Hasanah, Hijratul; Pratama, Sandi Fransisco; Dwijayanti, Endah; Satria, Rijal; Razak, Abdul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The Sumatran striped rabbit (Nesolagus netscheri) is endemic to the highland forests of Sumatra. This study aims to analyze the level of awareness and knowledge of universamong students about the endangered species Nesolagus netscheri, whose population is easingly threatened. This species has high ecological value, but the lack of information and knowledge about this species can worsen its condition in nature. This study used a survey approach by distributing questionna to junior and senior high school students in West Sumatra to measure their understanding of this species. The results showed that students' knowledge of the Sumatran Striped Rabbit is relatively low, although they have an awareness of the importance of conservation of endangered species. In conclusion, there is a need to improve specific environmental education programs to introduce local biodiversity to the younger generation. We suggest that by increasing student awareness and knowledge will encourage active participation in the conservation of this species and their environment in the future.